Differential CircRNA Expression Signatures May Serve as Potential Novel Biomarkers in Prostate Cancer - Greene, John; Baird, Anne-Marie; Lim, Marvin; Flynn, Joshua; McNevin, Ciara; Brady, Lauren; Sheils, Orla; Gray, Steven G.; McDermott, Raymond; Finn, Stephen P. (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs), a recently discovered non-coding RNA, have a number of functions including the regulation of miRNA expression. They have been detected in a number of malignancies including prostate cancer (PCa). The differential expression pattern of circRNAs associated with PCa and androgen receptor (AR) status was investigated in this study. circRNA profiling was performed using a high throughout microarray assay on a panel of prostate cell lines, which consisted of normal, benign, and malignant cells (n = 9). circRNAs were more commonly significantly up-regulated (p < 0.05) than downregulated in malignant cell lines (n = 3,409) vs. benign cell lines (n = 2,949). In a grouped analysis based on AR status, there were 2,127 down-regulated circRNAs in androgen independent cell lines compared to 2,236 in androgen dependent cell lines, thus identifying a potential circRNA signature reflective of androgen dependency. Through a bioinformatics approach, the parental genes associated with the top 10 differentially expressed circRNAs were identified such as hsa_circ_0064644, whose predicted parental gene target is RBMS3, and hsa_circ_0060539, whose predicted gene target is SDC4. Furthermore, we identified three circRNAs associated with the parental gene Caprin1 (hsa_circ_0021652, hsa_circ_0000288, and hsa_circ_0021647). Other studies have shown the importance of Caprin1 in PCa cell survival and drug resistance. Given the modified circRNA expression signatures identified here, these hypothesis generating results suggest that circRNAs may serve as potential putative diagnostic and predictive markers in PCa. However, further validation studies are required to assess the true potential of these markers in the clinical setting.